Model of Swamp and Peat Area Protection Policy Based on Justice and Local Community Empowerment - Wijoseno, Taufik; Yulianingrum, Aullia Vivi; Elviandri, Elviandri (Fakultas Syariah INSURI Ponorogo, 2024)
Peatland management in Kutai Kartanegara faces major challenges, especially due to the expansion of the coal mining industry. Regional Regulation No. 1 of 2016 is designed to protect peat swamp ecosystems and support the welfare of local communities, but its effectiveness is questionable amid the rapid exploitation of natural resources. This study aims to evaluate the effectiveness of the 2016 Regional Regulation in maintaining ecological and social balance through normative juridical law analysis that includes related laws and John Rawls' distributive justice theory approach. The Normative Juridical Citation Method and data are collected from primary legal sources, including Law Number 26 of 2007 concerning Spatial Planning, Law Number 3 of 2020 concerning Amendments to Law Number 4 of 2009 concerning Mineral and Coal Mining, as well as Kutai Kartanegara Regional Regulation Number 1 of 2016 itself and secondary legal sources in the form of relevant literature, such as books, journals, articles and internet sources as well as mass media, both print and online and allow data triangulation to be carried out. The study results show that weak supervision and the absence of strict sanctions for mining companies hinder the optimal implementation of the Regional Regulation, causing adverse impacts on the environment and community welfare. The analysis shows that these regulations are not entirely fair to local communities that are vulnerable to the negative impacts of the mining industry. This study recommends the revision of the Regional Regulation to add strict environmental sanctions provisions and strengthen community participation in peatland management to achieve ecological justice that is in line with regional economic development.